Measuring Quality of Life Under Spatial Frictions - Gabriel M. Ahlfeldt; Fabian Bald; Duncan H.W. Roth; Tobias Seidel (Institute of Labor Economics (IZA), 2024)
Using a quantitative spatial model as a data-generating process, we explore how spatial frictions affect the measurement of quality of life. We find that under a canonical parameterization, mobility frictions - generated by idiosyncratic tastes and local ties - dominate trade frictions - generated by trade costs and non-tradable services - as a source of measurement error in the Rosen-Roback framework. This non-classical measurement error leads to a downward bias in estimates of the urban quality-of-life premium. Our application to Germany reveals that accounting for spatial frictions results in larger quality-of-life differences, different quality-of-life rankings, and an urban quality-of-life premium that exceeds the urban wage premium.
Keywords: J2; J3; R2; R3; R5; 330; housing; spatial frictions; rents; prices; productivity; quality of life; spatial equilibrium; wages